1998
DOI: 10.1128/jvi.72.3.2352-2363.1998
|View full text |Cite
|
Sign up to set email alerts
|

The R33 G Protein-Coupled Receptor Gene of Rat Cytomegalovirus Plays an Essential Role in the Pathogenesis of Viral Infection

Abstract: We have identified a rat cytomegalovirus (RCMV) gene that encodes a G-protein-coupled receptor (GCR) homolog. This gene (R33) belongs to a family that includes the human cytomegalovirus UL33 gene. R33 was found to be transcribed during the late phase of RCMV infection in rat embryo fibroblasts. Unlike the mRNAs from all the other members of the UL33 family that have been studied to date, the R33 mRNA is not spliced. To study the function of the R33 gene, we constructed an RCMV strain in which the R33 open read… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(53 citation statements)
references
References 52 publications
1
52
0
Order By: Relevance
“…of 0.01. Previous studies of M78 in MCMV and homologues in rat CMV (RCMV: R78) and HCMV (UL78) have indicated that a loss of gene function resulted in replication defects in tissue culture; for the rodent counterparts a deficiency in salivary gland tropism in vivo was also observed (Beisser et al, 1998;O'Connor & Shenk, 2012;Oliveira & Shenk, 2001). Multi-step growth analysis showed that M78-LUC grew to wt MCMV levels in each cell type ( Fig.…”
Section: Recombinant M78-luc Virus Is Not Attenuated In Vitro or In Vivomentioning
confidence: 84%
“…of 0.01. Previous studies of M78 in MCMV and homologues in rat CMV (RCMV: R78) and HCMV (UL78) have indicated that a loss of gene function resulted in replication defects in tissue culture; for the rodent counterparts a deficiency in salivary gland tropism in vivo was also observed (Beisser et al, 1998;O'Connor & Shenk, 2012;Oliveira & Shenk, 2001). Multi-step growth analysis showed that M78-LUC grew to wt MCMV levels in each cell type ( Fig.…”
Section: Recombinant M78-luc Virus Is Not Attenuated In Vitro or In Vivomentioning
confidence: 84%
“…The mutant strain RCMVΔR33 could not be detected from the salivary glands as opposed to normal RCMV so the normal pathobiology of the infection is altered. Although a similar amount of DNA was observed in allografts of mutant RCMVΔR33‐ and normal RCMV‐infected recipients, the authors have previously shown that mutant RCMVΔR33 could not be detected in salivary glands of infected immunocompromised rats either by plaque assay or immunohistochemistry, although viral DNA could be detected up to 14 days after infection (2). Beisser et al discussed that it is possible that the ability to detect RCMV DNA in salivary glands early after infection is not the actual result of infection of salivary gland cells but instead the result of the presence of RCMV DNA‐containing circulating cells that pass through blood vessels of salivary glands (2).…”
mentioning
confidence: 87%
“…However, the mechanisms by which CMV enhances cardiac allograft arteriosclerosis are incompletely understood. In an article published in this issue, Streblow et al have investigated the role of CMV‐encoded chemokine receptors in cardiac allograft arteriosclerosis in a rat heart transplant model using a mutant strain of rat CMV (RCMV) that lacks the R33 open reading frame (RCMVΔR33) (2). The R33 chemokine receptor is a functional homologue of the HCMV encoded chemokine receptor US28.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A low level of replication was detectable in spleen and liver suggesting that the M33 gene product plays a role in dissemination to or replication in salivary glands [76]. A similar rat CMV mutant (R33) was transported normally to the salivary glands but was unable to enter or replicate in the salivary glands [77]. A number of other genes a¡ect replication in this organ.…”
Section: Tissue Tropismmentioning
confidence: 99%